Electrochemical Oxidation of Para-Aminophenol With Rare Earth Doped Lead Dioxide Electrodes: Kinetics Modeling and Mechanism - Weng, Mili; Yu, Xihe (Frontiers in Chemistry, 2019)
In this study, La and Ce doped PbO2 electrodes were prepared and the characteristic of the electrodes were discussed with the help of structure analysis. The catalytic effects of the doped electrodes were explored through the degradation of para-aminophenol wastewater. The results showed that the para-aminophenol removal was 96.96%, 89.34% and 77.55% after 120 min treatment with Ce-PbO2, La-PbO2 and PbO2, respectively. The para-aminophenol enhanced degradation mechanism was discussed with rare earth element doping electrodes and a kinetic model was established based on radical reactions mechanism with genetic algorithm (GA) calculation. The reaction constants of these electrodes were calculated and the results showed that the reaction constant of Ce-PbO2 electrode was the highest, which indicated that Ce-PbO2 electrode could have a better treatment effect. The EE/O was used as the index of energy consumption efficiency and the results were calculated and compared. This paper could provide basic data and technique reference of the prediction the oxidation reaction process of different electrodes for the electrochemical oxidation application in wastewater treatment.